Research of the convenience of pumpkin powder usage in instant food for military forces - Bobel (Zinchenko), Inna; Shmatko, Daryna (My University, 2016)
Having conducted the current scientific analysis, we’ve made a conclusion that the use of pumpkin powder is appropriate while developing food concentrates for lunch of instant food for military forces. Pumpkin powder has a unique chemical composition and is useful for the human body, it is a source of biologically active substances. It also improves the work of kidneys and liver, cleanses the body of toxins, bad cholesterol. Провівши науковий аналіз, ми зробили висновок, що використання гарбузового порошку є доцільним при розробленні харчоконцентратів обідніх страв миттєвого приготування для харчування військовослужбовців. Гарбузовий порошок має унікальний хімічний склад та корисний для організму людини, є джерелом цінних біологічно активних речовин. Покращує роботу нирок та печінки, очищує організм від токсинів, холестерину та шлаків.
Keywords: pumpkin powder; food concentrates; military forces; chemical composition; гарбузовий порошок; харчові концентрати; військовослужбовці; хімічний склад; кафедра технології хлібопекарських і кондитерських виробів; тыквенный порошок; пищевые концентраты; военнослужащие; химический состав